A systematic review of eHealth and mHealth interventions for lymphedema patients - Andrea Mangion; Bruno Ivasic; Neil Piller (Clinical eHealth)
Lymphedema is a chronic inflammatory disease that causes chronic swelling in the affected area, necessitating daily treatment. Millions of people worldwide are affected. The investigation of strategies to improve the overall health of patients, such as through the utilisation of electronic health (eHealth), is justified considering the ongoing burden of daily self-care. This research aimed to (a) identify current published research in eHealth and mobile health (mHealth) interventions for patients living with lymphedema; (b) assess feasibility and efficacy of the interventions; and (c) understand whether intervention adherence was affected by using eHealth. A systematic review was undertaken. Seven databases including MEDLINE, Scopus, Web of Science, CINAHL, the Cochrane Library, PsycINFO and IEEE Xplore were searched. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses were used. 1857 studies were identified through the database search with 9 meeting the inclusion criteria for a total of 1031 participants. There were 3 types of eHealth, including instructive online content, telehealth, and digital gaming. The efficacy of various eHealth and mHealth modalities was demonstrated in areas such as lymphedema outcomes, self-care, psychosocial outcomes, and disease comprehension. Reports of feasibility demonstrated that eHealth modalities were generally well accepted or preferred over conventional methods. 7 studies reported or discussed adherence and provided insight into the relationship between the design of the eHealth tool and the completion of the intervention. Several distinct categories of eHealth and mHealth interventions were shown to improve disease comprehension, psychosocial and lymphedema outcomes. Findings from this systematic review may have an impact on the design of future studies in this domain, including consideration of early user acceptance testing when developing eHealth tools. With the ongoing progress in eHealth technology, further investigation into eHealth is warranted given the encouraging results observed in a limited number of studies.